Effect of probiotics on C-reactive protein levels in schizophrenia: Evidence from a systematic review and meta-analysis - Verónica Romero-Ferreiro; Lorena García-Fernández; José Miguel Biscaia; Carmen Romero; Rocío González-Soltero; Mónica De la Fuente; Miguel A. Álvarez-Mon; Rolf Wynn; Roberto Rodriguez-Jimenez (Complementary Therapies in Medicine)
Background: Inflammatory markers play a pivotal role in schizophrenia, as they provide insight into the neuroinflammatory processes occurring in the context of the disorder. Elevated levels of these markers, particularly C-reactive protein (CRP), can indicate an underlying immune system dysregulation, potentially influencing symptom severity and progression. Recognizing these markers has led to investigate the use of probiotics as an adjuvant to improve the treatment of schizophrenia. The main objective of this study is to rigorously evaluate the efficacy of probiotics in reducing plasma levels of CRP in patients with schizophrenia. Methods: A systematic search and meta-analysis were conducted to review randomized clinical trials following the PRISMA methodology. The following search strategy ((SCHIZO* OR PSYCHOTIC OR PSYCHOSES) AND (PROBIOTIC* OR BIFIDOBACTER* OR LACTOBACILL*)) was used for searching publications between June-December 2024 on the PubMed, Web of Science, and APA PsycINFO databases. Individual study quality was assessed with the Cochrane risk of bias (RoB2) and the certainty of total evidence was assessed with the GRADE system. Results: The primary outcome assessed was the impact of probiotic supplementation on plasma CRP levels. Out of 78 studies initially identified, 4 were finally included in the meta-analysis. Three out four studies found a significant reduction in high-sensitivity C-reactive protein levels in the supplemented compared with the placebo group. The pooled analysis revealed a significant reduction in CRP levels with probiotic supplementation, with a standardized mean difference (SMD) of −0.46, (95 % CI −0.719; −0.201; p = 0.001). Conclusions: The synthesis and meta-analysis of available literature provide evidence for the potential role of probiotics in the reduction of serum CRP in schizophrenia compared with placebo. However, more clinical trials with better control of experimental design are needed before a clear recommendation as adjuvant therapy can be made.